The Influence of Capital Intensity and Thin Capitalization on Tax Avoidance Moderated by Profitability - Julianti, Julianti; Ruslim, Herman (Indonesian Journal of Multidisciplinary Science, 2023)
The purpose of this research is to examine the effect of capital intensity and thin capitalization on tax avoidance with profitability as a moderating variable. The sample for this study was selected using a purposive sampling method where the data used was 116 data from manufacturing companies in the consumer goods industry sector that were listed on the Indonesia Stock Exchange (IDX) consistently from 2018 to 2021. Research data analysis was assisted with the Econometric Views (EViews) software program. The results of the study show that capital intensity and thin capitalization have a positive effect on tax avoidance, profitability does not moderate the effect of capital intensity on tax avoidance and profitability can weaken the effect of thin capitalization on tax avoidance.